2021
DOI: 10.3390/en14217090
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Recycling in the Iron and Steel Industry via Power-to-Gas and Oxy-Fuel Combustion

Abstract: The iron and steel industry is the largest energy-consuming sector in the world. It is responsible for emitting 4–5% of the total anthropogenic CO2. As an energy-intensive industry, it is essential that the iron and steel sector accomplishes important carbon emission reduction. Carbon capture is one of the most promising alternatives to achieve this aim. Moreover, if carbon utilization via power-to-gas is integrated with carbon capture, there could be a significant increase in the interest of this alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Thus, in overall terms, the CO 2 is diminished by 71 kg CO2 /t HM with respect to the base case by using 1.93 GJ/t HM of electricity in the electrolyzer, so the energy penalty of the CO 2 avoidance is 27.1 MJ/kg CO2 . This value is line with the results of Perpiñán et al 8 for similar PtG integrations in the steel industry (he reported 34 MJ/kg CO2 ). Actually, since we have cut the coke consumption by 22.8 kg/t HM , which, in terms of electricity, is equivalent to a reduction of 0.24 GJ/t HM (assuming a coke heating value of 27.3 MJ/kg and a subcritical power plant net efficiency of 38% 31 ), and additionally we diminished the O 2 that has to be produced in the air separation unit by 77 kg O2 /t HM (we need inject 10 kg O2 /t HM more than in the base but we have 87 kg O2 /t HM available from electrolysis), which translates into a reduction of 0.05 MJ/t HM of electric consumption (assuming a typical ASU specific consumption of 0.61 MJ/kg O2 32 ), the net energy penalization of the CO 2 avoidance becomes 23.1 MJ/kg CO2 .…”
Section: Predicting the Operating Line For An Oxygen Blast Furnace In...supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, in overall terms, the CO 2 is diminished by 71 kg CO2 /t HM with respect to the base case by using 1.93 GJ/t HM of electricity in the electrolyzer, so the energy penalty of the CO 2 avoidance is 27.1 MJ/kg CO2 . This value is line with the results of Perpiñán et al 8 for similar PtG integrations in the steel industry (he reported 34 MJ/kg CO2 ). Actually, since we have cut the coke consumption by 22.8 kg/t HM , which, in terms of electricity, is equivalent to a reduction of 0.24 GJ/t HM (assuming a coke heating value of 27.3 MJ/kg and a subcritical power plant net efficiency of 38% 31 ), and additionally we diminished the O 2 that has to be produced in the air separation unit by 77 kg O2 /t HM (we need inject 10 kg O2 /t HM more than in the base but we have 87 kg O2 /t HM available from electrolysis), which translates into a reduction of 0.05 MJ/t HM of electric consumption (assuming a typical ASU specific consumption of 0.61 MJ/kg O2 32 ), the net energy penalization of the CO 2 avoidance becomes 23.1 MJ/kg CO2 .…”
Section: Predicting the Operating Line For An Oxygen Blast Furnace In...supporting
confidence: 92%
“…Since water electrolysis of the PtG process by-produces O 2 , it allows diminishing the electricity consumption of the air separation unit that feeds the OBF. A first approach to this OBF–PtG system was studied by Perpiñán et al 8 by using overall energy and mass balances. Assuming 430 MW electrolysis power capacity, they found a CO 2 emission reduction of 8% and specific electricity consumptions of 34 MJ/kg CO2 .…”
Section: Introductionmentioning
confidence: 99%
“…The main studies on methanation from steelworks POGs refer to use of COG [43,44], which, however, decreases the availability of the most suitable POG for internal heating and power production. Furthermore, only preliminary investigations can be found on the use of BFG and BOFG [45,46], including some works of the authors that were the basis of the investigation presented in this work [47,48].…”
Section: State-of-the-art Analysismentioning
confidence: 99%
“…Because of the requirement of high-temperature heat (above 800-1200 • C) and the nature of the process itself (CO 2 release during reduction), the blast furnace ironmaking process cannot be decarbonized with electrification [8]. Within this framework, some authors have studied the utilization of syngas and renewable fuels in the blast furnace [8][9][10]. Syngas is a CO 2 -neutral fuel gas that is synthetically obtained and is commonly constituted of carbon monoxide, hydrogen and carbon dioxide (the CO 2 -neutrality extent will depend on the raw material used for the syngas production).…”
Section: Introductionmentioning
confidence: 99%